Use Of Informatıon And Communıcatıon Technology (Ict) Devıces For Instructıonal Delıvery In Secondary Schools In Ebonyı State Of Nıgerıa - S. N Aja; P. I. Eze (European Scientific Journal, ESJ, 2016)
The study examined teachers perceptions on the use of information and communication technology (ICT) devices for instructional delivery in secondary schools in Ebonyi State, Nigeria. Four research questions guided the study. The population of the study comprised of all the three thousand two hundred and eighty-five (3,285) teacher in the two hundred and twenty-one (221) public secondary schools in Ebonyi State. Simple random sampling technique was used to select (8) teachers each from ninety schools used for the study to give a sample of seven hundred and twenty (720) respondents. The instrument used for data collection was structured questionnaire. Pearson’s Moment Correlation Co-efficient was used to calculate the reliability co-efficient of the pilot tests to get established reliability value of 0.79. The data collected were analysed using mean scores. It was found among other things that ICT devices are not adequately available, most available ICT devices are not in good working condition in schools studied, hence they are not adequately used and above all trained personnel are not also adequately available to operate the functional ones. Government through her appropriate agencies should as a matter of urgency procure and distribute the necessary ICT devices to secondary schools, more trained personnel should be recruited but for the interim the available ones could be retrained through short term holiday programmes, workshops and conferences to ensure adequate use and maintenance of these ICT devices as this will go a long way in improving instructional delivery in Ebonyi State Secondary Schools.